The voyage of the Dawn Treader - Lewis, C. S. (Clive Staples) 1898-1963.; Baynes, Pauline (New York HarperTrophy, 1980)
Lucy and Edmund, accompanied by their peevish cousin Eustace, sail to the land of Narnia where Eustace is temporarily transformed into a green dragon because of his selfish behavior and skepticism.
Keywords: Fantasy